Research on Efficient Coordination Control System of Virtual Coupling for Urban Rail Train - SHI Ke; WANG Yue; ZHANG Zhengfang; ZHOU Zhiwen; BAI Jinglei; LUO Qinyang (Kongzhi Yu Xinxi Jishu, 2024)
Virtual coupling of urban rail train sets represents a cutting-edge frontier in urban rail transit research, with the goal of improving operational efficiency of trains on the existing lines, particularly in the starting and stopping stages. This paper proposes an efficient collaborative control system for virtual coupling. Firstly, a model was constructed to simulate relative braking between urban rail train sets and it was used to generate relative braking distances between trains virtually coupled. Next, an efficient starting and stopping objective function was constructed at the collaborative control layer, and an optimized controller was devised to solve the objective function under constraints, generating key decision-making information for the leading and following trains during the starting and stopping stages. Subsequently, this study focused on the operation sequence planning technology, yielding the executable operation sequences of the leading and following trains, respectively. Finally, an LQR controller was designed, enabling the accurate following and control of operation sequences and the generation of execution instructions. Simulation results showed that the proposed control system for virtual coupling could achieve a parking time interval of less than 1.6s between the leading and following trains in urban rail transit within a speed range of 0~60 km/h, effectively improving the operational efficiency of virtually coupled urban rail train sets during the starting and stopping stages.